Obstructive Sleep Apnea and Cardiovascular Events After Percutaneous Coronary Intervention - Lee, Chi-Hang; Sethi, Rishi; Li, Ruogu; Ho, Hee-Hwa; Hein, Thet; Jim, Man-Hong; Loo, Germaine; Koo, Chieh-Yang; Gao, Xiao-Fei; Chandra, Sharad; Yang, Xiao-Xiao; Furlan, Sofia F.; et al. (Circulation (New York, N.Y.), 2016)
BACKGROUND—There is a paucity of data from large cohort studies examining the prognostic significance of obstructive sleep apnea (OSA) in patients with coronary artery disease. We hypothesized that OSA predicts subsequent major adverse cardiac and cerebrovascular events (MACCEs) in patients undergoing percutaneous coronary intervention. METHODS AND RESULTS—The Sleep and Stent Study was a prospective, multicenter registry of patients successfully treated with percutaneous coronary intervention in 5 countries. Between December 2011 and April 2014, 1748 eligible patients were prospectively enrolled. The 1311 patients who completed a sleep study within 7 days of percutaneous coronary intervention formed the cohort for this analysis. Drug-eluting stents were used in 80.1% and bioresorbable vascular scaffolds in 6.3% of the patients, and OSA, defined as an apnea-hypopnea index of ≥15 events per hour, was found in 45.3%. MACCEs, a composite of cardiovascular mortality, nonfatal myocardial infarction, nonfatal stroke, and unplanned revascularization, occurred in 141 patients during the median follow-up of 1.9 years (interquartile range, 0.8 years). The crude incidence of an MACCEs was higher in the OSA than the non-OSA group (3-year estimate, 18.9% versus 14.0%; p=0.001). Multivariate Cox regression analysis indicated that OSA was a predictor of MACCEs, with an adjusted hazard ratio of 1.57 (95% confidence interval, 1.10–2.24; P=0.013), independently of age, sex, ethnicity, body mass index, diabetes mellitus, and hypertension. CONCLUSIONS—OSA is independently associated with subsequent MACCEs in patients undergoing percutaneous coronary intervention. Evaluation of therapeutic approaches to mitigate OSA-associated risk is warranted. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierNCT01306526.